Regulation of AKT Phosphorylation at Ser473 and Thr308 by Endoplasmic Reticulum Stress Modulates Substrate Specificity in a Severity Dependent Manner - Yung, Hong Wa; Charnock-Jones, D. Stephen; Burton, Graham J. (PLOS ONE, 2011)
Endoplasmic reticulum (ER) stress is a common factor in the pathophysiology of diverse human diseases that are characterised by contrasting cellular behaviours, from proliferation in cancer to apoptosis in neurodegenerative disorders. Coincidently, dysregulation of AKT/PKB activity, which is the central regulator of cell growth, proliferation and survival, is often associated with the same diseases. Here, we demonstrate that ER stress modulates AKT substrate specificity in a severity-dependent manner, as shown by phospho-specific antibodies against known AKT targets. ER stress also reduces both total and phosphorylated AKT in a severity-dependent manner, without affecting activity of the upstream kinase PDK1. Normalisation to total AKT revealed that under ER stress phosphorylation of Thr308 is suppressed while that of Ser473 is increased. ER stress induces GRP78, and siRNA-mediated knock-down of GRP78 enhances phosphorylation at Ser473 by 3.6 fold, but not at Thr308. Substrate specificity is again altered. An in-situ proximity ligation assay revealed a physical interaction between GRP78 and AKT at the plasma membrane of cells following induction of ER stress. Staining was weak in cells with normal nuclear morphology but stronger in those displaying rounded, condensed nuclei. Co-immunoprecipitation of GRP78 and P-AKT(Ser473) confirmed the immuno-complex consists of non-phosphorylated AKT (Ser473 and Thr308). The interaction is likely specific as AKT did not bind to all molecular chaperones, and GRP78 did not bind to p70 S6 kinase. These findings provide one mechanistic explanation for how ER stress contributes to human pathologies demonstrating contrasting cell fates via modulation of AKT signalling.